Energy Efficient Dryer with Rice Husk Fuel for Agriculture Drying - M. Djaeni; N. Asiah; S Suherman; A. Sutanto; A. Nurhasanah (Center of Biomass & Renewable Energy (CBIORE), 2015)
Energy usage is crucial aspect on agriculture drying process. This step spends about 70% of total energy in post harvest treatment. The design of efficient dryer with renewable energy source is urgently required due to the limitation of fossil fuel energy. This work discusses the performance of air dehumidification using rice husk fuel as heat source for onion, and paddy drying. Unlike conventional dryer, the humidity of air during the drying was dehumidified by adsorbent. Hence, the driving force of drying can be kept high. As consequences, the drying time and energy usage can be reduced. Here, the research was conducted in two step: laboratory and pilot scale tests. Results showed that the lowering air humidity with rice husk fuel has improved the energy efficiency. At operational temperature 60oC, the heat efficiency of 75% was achieved.